2019
DOI: 10.1177/1945892419844459
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene Receptor Antagonist Addition to H1-Antihistamine Is Effective for Treating Allergic Rhinitis: A Systematic Review and Meta-analysis

Abstract: Background Histamine and leukotriene are released after being triggered by allergen exposure. The combination of leukotriene receptor antagonist (LTRA) and H1-antihistamine (AH) is utilized to control the allergic rhinitis (AR) symptoms after the failure of either AH or LTRA. Objective This study aimed to investigate the effects of the combination of H1-antihistamine and leukotriene receptor antagonist (AH-LTRA) in patients with AR. Methods Randomized controlled trials studying the effects of AH-LTRA versus AH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“…The study also demonstrates the possibility that patients with perennial AR benefit more from combination therapy [126]. Another study also shows that combination therapy with LTRA + SAH provides greater beneficial effects against composite nasal symptoms, rhinorrhea, sneezing, and rhinoconjunctivitis symptoms in patients with AR and patients with perennial AR [127].…”
Section: Lts and Allergic Diseasesmentioning
confidence: 97%
“…The study also demonstrates the possibility that patients with perennial AR benefit more from combination therapy [126]. Another study also shows that combination therapy with LTRA + SAH provides greater beneficial effects against composite nasal symptoms, rhinorrhea, sneezing, and rhinoconjunctivitis symptoms in patients with AR and patients with perennial AR [127].…”
Section: Lts and Allergic Diseasesmentioning
confidence: 97%
“…A meta-analysis study showed higher efficacy of leukotriene receptor antagonist compared with H1 antihistamines during nighttime symptoms but not in daytime symptoms ( 100 ). Other meta-analysis studies demonstrated that combination therapy of leukotriene receptor antagonist plus H1 antihistamines conferred increased efficacy in reducing daytime symptoms ( 101 , 102 ).…”
Section: Treatment Of Allergic Rhinitismentioning
confidence: 99%
“…The findings of our meta-analysis do not recom- as or less effective than oral antihistamines for AR (34) ; moreover, it is less effective than INCS2. LTRA combined with oral H1 antihistamine might be considered when failure of antihistamine monotherapy (2,32,35) . In this situation, the formulation MP-AzeFlu of INCS is better evidence-based option validated by previous studies (36) , meta-analysis (37,38) , and clinical guidelines (33,39) .…”
Section: Discussionmentioning
confidence: 99%